EFFECTIVENESS OF THE IMPLEMENTATION OF LEGAL REGULATIONS ON PEOPLE'S BUSINESS CREDIT ON THE INCREASE OF MICRO, SMALL, AND MEDIUM ENTERPRISES (Case Study of PT Bank Mandiri Binjai Branch) - Shaila Aulia Prilini; M. Rizal, M. Hum (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
People's Business Credit (KUR) is a government policy aimed at expanding access to financing for Micro, Small and Medium Enterprises (MSMEs). Even though it is supported by various regulations, the implementation of KUR still faces problems, especially regarding the application of the precautionary principle, understanding additional collateral, and the effectiveness of legal protection for debtors. This research aims to analyze the effectiveness of the implementation of KUR legal regulations at PT Bank Mandiri Binjai Branch, its conformity with statutory provisions, and the effectiveness of its implementation based on Soerjono Soekanto's theory of legal effectiveness. The research uses empirical juridical methods with a descriptive analytical approach. Primary data was obtained through interviews and observations, while secondary data was obtained through literature study of relevant laws and regulations, books, journals and literature. The research results show that the implementation of KUR at PT Bank Mandiri Binjai Branch is in accordance with Law Number 10 of 1998 concerning Banking, Law Number 20 of 2008 concerning MSMEs, Government Regulation Number 7 of 2021, and Regulation of the Coordinating Minister for Economic Affairs Number 3 of 2024. The application of the precautionary principle is carried out through business feasibility analysis, field surveys, credit history checks, and the application of moral obligations that are not categorized as collateral. additional. Based on the analysis of legal effectiveness theory, the implementation of KUR regulations has been effective from the aspects of law, law enforcement, facilities, society and culture, although increased socialization is still needed to strengthen public understanding of KUR provisions.